Application of molecular genetics method for differentiating Martes zibellina L. heart from its adulterants in traditional Chinese medicine based on mitochondrial cytochrome b gene. (February 2014) - Li, Mingcheng; Xia, Wei; Wang, Miao; Yang, Mingyan; Zhang, Lihua; Guo, Jie
Abstract The use of Martes zibellina L. heart as a famous kind of traditional Chinese medicine has been documented for many years in China. Identification of its authenticity as raw materials became a key in controlling of herbal preparations. In this study, the characteristics of mitochondrial cytochrome b (Cyt b) gene from four species of Martes were explored, and a specific molecular genetics technique for identifying the heart of M. zibellina L. in addition to some close relatives from their counterfeits was established. The bioinformatics was carried out to design the primers for the Cyt b gene based on the different species of Martes. PCR and sequencing technology were performed. The mt DNA was extracted from all of fresh M. zibellina L., Martes melampus. Martes flavigula. Martes martes heart samples and dry M. zibellina L. heart powder through the modified alkaline extracting method in addition to its counterfeits including the chicken heart, duck heart, goose heart, rabbit heart and Mustela vison. The complete mt DNA was separated from all samples used in the study, and the Cyt b gene with 310 bp segments was amplified only from M. zibellina L. heart as DNA template by the PCR technique. The sequencing indicated that the segment amplified by the PCR was homologous with the species of M. zibellina in GenBank. The data revealed that the primers and selected segment could be used as the genetic markers to identify M. zibellina L. heart from its counterfeits among different animal species.